Radiographic Assessment of Occurrence of Pulp Stones in Molars of Selected Adult Nepalese Populations at Tertiary Care Center - Acharya, N.; Chakradhar, A.; Kafle, D. (Kathmandu University Medical Journal, 2021)
Background Pulp stones or “denticles” are a frequent finding in coronal and radicular pulp of primary and permanent dentition. These discrete calcified bodies can be seen in a healthy, diseased and sometimes even in an unerupted tooth. These calcifications are mostly present in molars as free, attached or embedded to dentine of pulp chamber or root canals. Objective To determine the occurrence of pulp stones in molars of selected adult Nepalese population using radiographs and assess the association of its occurrence gender and arch wise. Method A descriptive cross-sectional study was performed using orthopantomogram of total 380 patients (190 male and 190 females) of age group ranging from 16-30 years by convenience sampling. Data were collected through the examination of both hard and soft copies of radiographs under magnification. Pulp stones were scored as present or absent and their association with gender and dental arch were recorded. Descriptive statistics and chi square test was performed to see the prevalence and to compare the occurrence of pulp stone respectively. Result Out of 380 radiographic samples, pulp stones were present in 41.05% of the samples. The occurrence of pulp stones were found to be higher in females than in males, although the difference was not statistically significant (p=0.060).The total number of teeth with pulp stones was 238 and 61 in maxillary and mandibular arches respectively, with statistically significant difference (p<0.001). Conclusion The overall occurrence of pulp stone was found to be 41.05%. It was observed more in females (45.78%) than in males (37%) and more frequently located in maxillary molars (29.2%) than in mandibular molars (8.2%).